Calitatea vieţii şi cultura - Urse, Laureana (Calitatea Vieții, 2008)
The present paper is the first part of a wider and more profound analysis of the relation between culture and the quality of life; the analysis consists of three chapters: I. Quality of life; II. Culture; III. Culture – quality of life. I. “Quality of life” includes the historical roots of the quality of life problematic and the actual problems of the quality of life. The historical roots are, generally, the concerns for people life, and, in particular, for people happiness. The paper presents Aristotle's opinion on happiness and they way the approach of happiness evolved, as presented by Petre Andrei. The paper presents, subsequently, the emergence of the quality of life concept, worldwide and in Romania. Explicit reference is made to the quality of life surveys conducted by the Institute for Quality of Life Research (brief presentation of the research, identifying the place of culture within this research). II. “Culture”, consists of an attempt to answer the question “What is culture?” by presenting several approaches and definitions of the culture. The cultural globalization is also approached, evaluating the importance of this phenomenon from the perspective of the relation between culture and quality of life. III. Finally, the paper presents the first considerations on the relationship between culture – quality of life: the main dimensions of the culture bearing a direct impact on the quality of life are presented. The subsequent scientific approach will also attempt to reveal other perspectives of analysis of the relationship between culture and the quality of life.